Future generation information technology Third International Conference, FGIT 2011 in Conjunction with GDC 2011, Jeju Island, Korea, December 8-10, 2011. Proceedings - FGIT (Conference) (2011 Cheju Island, Korea); Kim, Tai-hoon.; Adeli, Hojjat; Slezak, Dominik; Sandnes, Frode Eika.; Song, Xiaofeng; Chung, Kyo-il.; Arnett, Kirk P.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book comprises selected papers of the Third International Conference on Future Generation Information Technology, FGIT 2011, held in Jeju Island, Korea, in December 2011. The papers presented were carefully reviewed and selected from numerous submissions and focuse on the various aspects of advances in information technology. They were selected from the following 13 conferences: ASEA 2011, BSBT 2011, CA 2011, CES3 2011, DRBC 2011, DTA 2011, EL 2011, FGCN 2011, GDC 2011, MulGraB 2011, SecTech 2011, SIP 2011 and UNESST 2011.
Electronic reproduction.
Keywords: Computer science -- Congresses; Information technology -- Congresses; Electronic books